Analysis of mutagens from cooked foods by directly combined liquid chromatography-mass spectrometry. - Edmonds, C G (1986)
Directly combined high performance liquid chromatography-mass spectrometry (LC/MS) has been studied as a method of analysis of heterocyclic aromatic mutagens in cooked foods, in the parts per billion concentration range. Identification and semiquantitative estimation of mutagens is based on accurate measurement of chromatographic retention (k') and molecular weight-selective detection of mutagens, which are protonated during passage of the chromatographic eluant into a thermospray interface of a quadrupole mass spectrometer. Standard chromatographic retention (k') values in two reversed-phase systems and data from thermospray mass spectra from nine mutagens are reported. An isolation scheme employing CH3OH extraction, acid-base partition, cellulose-trisulfo-Cu-phthalocyanine adsorption, and normal-phase HPLC was used prior to LC/MS analysis. Initial applications have been demonstrated in the analysis of 2-amino-3-methylimidazo[4,5-f]quinoline (IQ) and 2-amino-3,4-dimethylimidazo[4,5-f]quinoline (MeIQ) in broiled salmon flesh. Levels measured were estimated to be in the range 0.2 to 0.4 microgram/kg IQ and 0.4 to 0.9 microgram/kg MeIQ. The method is judged to be generally applicable with minimal sample prefractionation to detection of mutagens at the parts per billion level in cooked foods.